2019
DOI: 10.1007/s13157-019-01198-z
|View full text |Cite
|
Sign up to set email alerts
|

A Basin-Wide Survey of Coastal Wetlands of the Laurentian Great Lakes: Development and Comparison of Water Quality Indices

Abstract: Coastal wetlands of the Laurentian Great Lakes are vital habitats for biota of ecological and economic importance. These habitats are susceptible to water quality impairments driven by runoff from the landscape due to their location along the shoreline. Monitoring of the overall status of biotic and abiotic conditions of coastal wetlands within the Great Lakes has been ongoing for over a decade. Here, we utilize measurements of aquatic physicochemical and land cover variables from 877 vegetation zones in 511 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
(55 reference statements)
0
11
0
Order By: Relevance
“…Modeling by Hamlin et al (2020) showed agricultural fertilizer to be a major nutrient source along the southern shore of Lake Ontario. Agricultural and urban land use in wetland catchments of the Great Lakes has been shown to affect nutrient enrichment, water clarity, and sediment quality (Crosbie and Chow-Fraser 1999;Trebitz et al 2007;Morrice et al 2008;Robertson and Saad 2011;Harrison et al 2020). In a basin-wide study, Lougheed et al (2001) concluded that the proportion of agricultural and urban land in wetland watersheds was a statistically significant predictor of water quality.…”
Section: Introductionmentioning
confidence: 99%
“…Modeling by Hamlin et al (2020) showed agricultural fertilizer to be a major nutrient source along the southern shore of Lake Ontario. Agricultural and urban land use in wetland catchments of the Great Lakes has been shown to affect nutrient enrichment, water clarity, and sediment quality (Crosbie and Chow-Fraser 1999;Trebitz et al 2007;Morrice et al 2008;Robertson and Saad 2011;Harrison et al 2020). In a basin-wide study, Lougheed et al (2001) concluded that the proportion of agricultural and urban land in wetland watersheds was a statistically significant predictor of water quality.…”
Section: Introductionmentioning
confidence: 99%
“…The U.S. Great Lakes coastal region has high N enrichment due to agricultural, atmospheric, and point-source inputs (Morrice et al 2008 ; National Atmospheric Deposition Program 2022 ). For example, atmospheric N deposition, especially the concentration of NH 4 + , into Great Lakes ecosystems have increased by 400% from historic levels (Du et al 2014 ), while dissolved inorganic N in Great Lakes coastal wetlands has risen as a direct result of row-crop agriculture and urbanization in the region (Morrice et al 2008 ; Harrison et al 2020 ). Understanding potential changes to Great Lakes ecosystems is essential for conservation of these ecosystems in the future.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts to assess, monitor, and restore GLCW have gained momentum over the last several decades (Smith et al 1991;Loftus et al 2004;Uzarski et al 2017a;Harrison et al 2019). The Great Lakes coastal wetland monitoring program (CWMP) has assessed over a thousand GLCW during the last decade and developed indices to quantify wetland condition.…”
Section: Introductionmentioning
confidence: 99%
“…The Great Lakes coastal wetland monitoring program (CWMP) has assessed over a thousand GLCW during the last decade and developed indices to quantify wetland condition. One such index, the CWMP water quality-land use indicator (hereafter the WQ-LU indicator; referred to as "SumRank" in earlier publications such as Cooper et al 2018, and Kovalenko et al 2019, incorporates many in situ water quality measurements and adjacent land-cover variables into a single score (Uzarski et al 2017a;Harrison et al 2019). Lower scores indicate poor wetland quality, while higher scores indicate less disturbed conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation